2014
DOI: 10.1021/ie5031453
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Bubble Absorption Enhancement in Water-Based Nanofluids

Abstract: Nanoparticles addition is a novel technique for enhancement of mass transfer in absorption process. A bubble column was used for investigation of hydrogen sulfide (H2S) absorption process. Silica and exfoliated graphene oxide (EGO) were used for preparation of nanofluids used as hydrogen sulfide absorbent. The absorption rate of hydrogen sulfide deteriorated by addition of 14 nm silica nanoparticles to water, while EGO–water nanofluid augmented hydrogen sulfide absorption relative to the base fluid. EGO–water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…In each section, performed studies, type of nanofluids, size and concentration range of nanoparticles, mass transfer measurement method, maximum observed enhancement and suggested mass transport mechanisms were pointed out [13]. In the field of mass transfer in nanofluids, there are a few researches dealt with mass diffusion in nanofluids [1,9,[14][15][16][17][18][19][20] and more researches investigated the influence of nanoparticles on convective mass transfer [10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Nevertheless, most researches on convective mass transfer in nanofluids are related to the gas absorption processes [21][22][23][24][25][26][27][28][29][30] and there have been limited attempts to use nanofluids in other popular separation processes such as liquid-liquid extraction [10,[34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…In each section, performed studies, type of nanofluids, size and concentration range of nanoparticles, mass transfer measurement method, maximum observed enhancement and suggested mass transport mechanisms were pointed out [13]. In the field of mass transfer in nanofluids, there are a few researches dealt with mass diffusion in nanofluids [1,9,[14][15][16][17][18][19][20] and more researches investigated the influence of nanoparticles on convective mass transfer [10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Nevertheless, most researches on convective mass transfer in nanofluids are related to the gas absorption processes [21][22][23][24][25][26][27][28][29][30] and there have been limited attempts to use nanofluids in other popular separation processes such as liquid-liquid extraction [10,[34][35][36]…”
Section: Introductionmentioning
confidence: 99%
“…For all nanoparticles types, the nanoparticles intensify the micro-convections, producing larger mass transfer rate in comparison to pure basefluid; thus, initial increase in CO 2 absorption would be rationalizable with the aforementioned nanoparticles mass fractions. On the other hands, increasing a number of nanoparticles leads to enhance further the viscosity of nanofluids, thereby overcoming the nanoparticles micro-convection impacts together with diminishing the absorption of CO 2 within the nanofluids [4,12]. Furthermore, Figure 5 clearly exhibits that CO 2 absorption molar flux in metal oxides-based nanofluids is larger than that in deionized water for various nanoparticles mass loads.…”
Section: Nanofluid Characterizationmentioning
confidence: 95%
“…Hence, in 1992, the United Nation Conference on Environment and Development offered a new strategy for reducing the emission of acidic and other greenhouse gases to below the standard level until 2000 [1]. Consequently, the governments should finance researchers and scholars to apply new methods and techniques to reduce the amount of CO 2 as well as the SO 2 produced from large-scale industries and sources [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles finally saturated interface at particle fraction of 0.05%, so for more nanoparticle concentrations, viscosity effects seem to be dominantly responsible for descending trend. Esmaeili Faraj et al's study[34] on absorption of H 2 S into silica nanofluid indicated reduction of absorption rate. They attributed their observation to two main reasons: (1) increasing the viscosity of nanofluid and (2) reduction of the effective fraction of the gas−liquid contact area because of suspended particles presence.…”
mentioning
confidence: 99%
“…They attributed their observation to two main reasons: (1) increasing the viscosity of nanofluid and (2) reduction of the effective fraction of the gas−liquid contact area because of suspended particles presence. Esmaeili Faraj et al[34] also investigate the influence of EGO (exfoliated graphene oxide nanoparticles) on absorption rate of H 2 S and observed peak enhancement of 40% using 0.02 wt. % EGO and faced a decreasing trend after this concentration.…”
mentioning
confidence: 99%